2018
DOI: 10.3892/ol.2018.7906
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1 is involved in regulating HER2-positive breast cancer radiosensitivity by controlling EMT

Abstract: Abstract. Breast cancer is a malignant tumor that can rapidly progress to cancer for which there are limited therapeutic options. The aim of the present study was to examine the regulatory mechanism of human epidermal growth factor receptor 2 (HER2)-positive breast cancer radiosensitivity by comparing the protein expression levels of HER2 in breast cancer cell lines. Breast cancer cell line MCF-7 (low HER2 expression) and breast cancer cell lines ZR-7530 and SK-BR-3 (high HER2 expression) were selected for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
3
0
0
Order By: Relevance
“…Moreover, we observed a trend toward higher expression of SNHG3 in HER2‐positive tumors compared with the HER2‐negative ones. This finding is in accordance with the results of a recent study, which demonstrated that expression of ZEB1, an upregulated gene by SNHG3 , has been shown to be positively correlated with HER2 expression (Han, Zhu, Xu, Shui, & Lu, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, we observed a trend toward higher expression of SNHG3 in HER2‐positive tumors compared with the HER2‐negative ones. This finding is in accordance with the results of a recent study, which demonstrated that expression of ZEB1, an upregulated gene by SNHG3 , has been shown to be positively correlated with HER2 expression (Han, Zhu, Xu, Shui, & Lu, ).…”
Section: Discussionsupporting
confidence: 93%
“…mTOR: mechanistic target of rapamycin; ROC: receiver operating characteristic; SNHG1: small nucleolar RNA host gene 1 [Color figure can be viewed at wileyonlinelibrary.com] expression of SNHG3 in HER2-positive tumors compared with the HER2negative ones. This finding is in accordance with the results of a recent study, which demonstrated that expression of ZEB1, an upregulated gene by SNHG3, has been shown to be positively correlated with HER2 expression(Han, Zhu, Xu, Shui, & Lu, 2018).…”
supporting
confidence: 93%
See 1 more Smart Citation